Long-term prognostic factors for PRRT in neuroendocrine tumors - Trautwein, Nils Florian; Schwenck, Johannes; Jacoby, Johann; Reischl, Gerald; Fiz, Francesco; Zender, Lars; Dittmann, Helmut; Hinterleitner, Martina; la Fougère, Christian (Frontiers in Medicine, 2023)
Aim/introduction Peptide receptor radionuclide therapy (PRRT) is an effective and well-tolerated treatment option for patients with neuroendocrine tumors (NETs) that prolongs progression-free survival (PFS). However, the limited overall survival (OS) rates in the prospective phase III study (NETTER1) highlighted the need to identify patient-specific long-term prognostic markers to avoid unnecessary side effects and enable better treatment stratification. Therefore, we retrospectively analyzed prognostic risk factors in NET patients treated with PRRT. Methods A total of 62 NET patients (G1: 33.9%, G2 62.9%, and G3 3.2%) with at least 2 cycles of PRRT with [177Lu]Lu-HA-DOTATATE (mean 4 cycles) were analyzed. Of which, 53 patients had primary tumors in the gastroenteropancreatic (GEP) system, 6 had bronchopulmonary NET, and 3 had NET of unknown origin. [68Ga]Ga-HA-DOTATATE PET/CT scans were performed before PRRT start and after the second treatment cycle. Different clinical laboratory parameters, as well as PET parameters, such as SUVmean, SUVmax, and PET-based molecular tumor volume (MTV), were collected, and their impact on the OS was investigated. Patient data with a mean follow-up of 62 months (range 20–105) were analyzed. Results According to interim PET/CT, 16 patients (25.8%) presented with partial response (PR), 38 (61.2%) with stable disease (SD), and 7 (11.3%) with progressive disease (PD). The 5-year OS was 61.8% for all patients, while bronchopulmonary NETs showed poorer OS than GEP-NETs. Multivariable Cox regression analysis showed that chromogranin A level and MTV together were highly significant predictors of therapeutic outcome (HR 2.67; 95% CI 1.41–4.91; p = 0.002). Treatment response was also influenced by the LDH level (HR 0.98; 95% CI 0.9–1.0; p = 0.007) and patient age (HR 1.15; 95% CI 1.08–1.23; p < 0.001). ROC analysis revealed baseline MTV > 112.5 ml [Sens. 91%; Spec. 50%; AUC 0.67 (95% CI 0.51–0.84, p = 0.043)] and chromogranin A >1,250.75 μg/l [Sens. 87%; Spec. 56%; AUC 0.73 (95% CI 0.57–0.88, p = 0.009)] as the best cutoff values for identifying patients with worse 5-year survival. Conclusion Our retrospective analysis defined MTV and chromogranin A in combination as significant prognostic factors for long-term OS. Furthermore, an interim PET/CT after two cycles has the potential in identifying non-responders who may benefit from a change in therapy at an early stage.